"أحاديث الأحكام المختلفة على سفيان الثوري بابدال الراوي وأثرها على اختلاف الفقهاء Variance of canonical Ahadith by Narrators of Sufian al-Thawri and its Impact on the Disagreement among the Jurists " - د۔محمد عمران; د۔ محمد انور (الإيضاح, 2018)
"The differences in the transmissions of the Hadith have great impact on the disagreement among the jurists, and this sets in the diversity in Fiqh. This research is about the disagreement of narrators from Imam Sufyan al-Thawri in the Asanid of Hadiths which are collected from the book “Ellal al-hadith by Imam al-Daraqutni”. The difference among the narrators exist in the Sanad by the change of narrator in the Sanad, and it results in the disagreement its impact on the various jurisprudential issues between Jurists Key words: Canonical Ahadith, Narrators of Sufian al-Thawri, Disagreement among the Jurists."